Prevalence and associated factors of dementia among elderly citizens living in old age homes of Kathmandu Valley. - Parajuli,Prashikchhya (2018)
ABSTRACT: Background: With advancement in modern medicine and health sector, the older population is rapidly increasing. That being said, research regarding their health and well being has barely been the point of focus. In addition to that, mental health has grabbed the attention of many researchers worldwide and even in Nepal. Thus a study that can help researchers and development agencies to access the prevalence of dementia in various old age homes of Kathmandu which help them cope with such problems is required. Objective: The overall objective of the study was to determine the prevalence of dementia and its associated factors among the senior citizens living in old age homes of Kathmandu Valley. Methodology: Cross sectional study was conducted among twelve functional old age homes of Kathmandu Valley. Complete enumerative sampling method was followed. Screening of the cognitive status including dementia was done using Nepali version of MMSE for literate respondents, while Six-CIT was used for both literate and illiterate respondents. Chi-square test was used to observe the association. Result: Among 304 residents (229 Females and 75 males) aged 77.54 + 9.53 years (mean + SD) were included. Six-CIT disclosed the fact that 37 (12.2%), 10 (3.3%), and 257 (84.5%) had no cognitive impairment, mild cognitive impairment and severe cognitive impairment respectively. Whereas in the midst of literate respondents, 27 (58.7%) had no cognitive impairment, 13 (28.3%) had mild cognitive impairment and 6 (13%) had severe cognitive impairment. Similarly, Chi square test revealed that dementia was associated with age (p = 0.004), gender (p <0.001), educational status (p <0.001), past occupation (p = 0.002), alcohol consumption (p = 0.042) and diabetes (p = 0.006). Conclusion: This study identified a significantly high prevalence of dementia in old age homes of Kathmandu Valley. With high prevalence of dementia, senior citizens in different old age homes need prompt attention and appropriate interventions. Keywords: Dementia, Prevalence, Associated factors, Senior citizens, Old age homes, Kathmandu Valley